Disentangling the roles of demographic and temporal trends in musculoskeletal disorders. (20th October 2021) - Bouziri, H; Descatha, A; Dab, W; Jean, K
Abstract: Background: Musculoskeletal disorders (MSDs) affect nearly 40 million European workers in 2017. Since age constitutes an important risk factor for MSDs, the overall aging of the working population is expected to influence the burden of disease. However, factors other than aging that may explain global trends in MSDs are unknown. We conducted a systematic review to summarise the evidence on the role of demographic and temporal changes in the occurrence of MSDs. Methods: Following the PRISMA guidelines, we searched Pubmed, ScienceDirect and Web of Science over the 1990-2020 period for articles reporting temporal trends in MSDs incidence or prevalence in the general working-age population. We only included articles controlling for age in the analysis. To assure the quality of the articles, the bias risk was assessed using the RoB-SPEO tool. The main indicators we extracted were age-controlled time trends in MSDs incidence or prevalence. Results: Among 966 articles, 16 fulfilled the inclusion criteria, representing 23 results according to the indicators extracted. No study was found with high risk of bias. Nine used a definition of MSDs based on pain and 14 based on repercussions on work or social life. Twelve results presented time trends in prevalence and 11 in incidence. After controlling for age, temporal trends in MSDs presented some heterogeneity. Indeed, 10 results documented increases and 12 reported non-monotonic changes. Only one result reported a decreasing trend in MSDs incidence. Several factors other than aging were suggested to explain temporal trends in MSDs, mainly trends in obesity, changing occupational exposures and cultural factors in tolerance to pain. Conclusions: This review shows that factors additional to aging of the working population may contribute to varying or increasing trends in MSDs. Results also highlight the scarcity of available evidence on time trends in MSDs burden and their underlying causes. Key messages: Despite a scarcity of evidence, our results suggest that factors additional to aging of the working population may contribute to varying or increasing trends in MSDs. Several factors other than aging were suggested to explain temporal trends in MSDs, mainly trends in obesity, changing occupational exposures and cultural factors in tolerance to pain.